2020
DOI: 10.1134/s2517751620050078
|View full text |Cite
|
Sign up to set email alerts
|

Features of Synthesis of Anion Exchange Matrix “Polikon A” with Oxidated Ultrafine Additives on Lavsan Textile Bases

Abstract: A comparative analysis of the studies on the influence of the textile structure of reinforcing fabric on the physicomechanical and sorption characteristics of anion-exchange systems as a component of the "Polikon" mosaic materials is presented in this study. This study shows the promise of using polyester fibers as a reinforcing fiber base for the production of Polikon A membrane materials. The morphology, moisture capacity, static exchange capacity, and physical and mechanical characteristics of anion-exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The chemical composition of Polikon A on the fabric from the polyester fiber was studied by the energy dispersive method (Figures 6-9). It was shown that the elemental composition was dominated by carbon (in weight%): 49.96 ± 0.37; nitrogen 17.17 Suffusion is a destructive process that occurs during the operation of membranes, expressed in the leeching of unrelated or loosely bound particles from the material into the solution [34]. To avoid suffusion, as well as to give the anion matrix "Polikon A" a more homogeneous cross-linked structure, it was proposed to introduce the oxidized ultrafine modifying additives of Fe, Ni, and Si oxides at the synthesis stage [34].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The chemical composition of Polikon A on the fabric from the polyester fiber was studied by the energy dispersive method (Figures 6-9). It was shown that the elemental composition was dominated by carbon (in weight%): 49.96 ± 0.37; nitrogen 17.17 Suffusion is a destructive process that occurs during the operation of membranes, expressed in the leeching of unrelated or loosely bound particles from the material into the solution [34]. To avoid suffusion, as well as to give the anion matrix "Polikon A" a more homogeneous cross-linked structure, it was proposed to introduce the oxidized ultrafine modifying additives of Fe, Ni, and Si oxides at the synthesis stage [34].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the elemental composition was dominated by carbon (in weight%): 49.96 ± 0.37; nitrogen 17.17 Suffusion is a destructive process that occurs during the operation of membranes, expressed in the leeching of unrelated or loosely bound particles from the material into the solution [34]. To avoid suffusion, as well as to give the anion matrix "Polikon A" a more homogeneous cross-linked structure, it was proposed to introduce the oxidized ultrafine modifying additives of Fe, Ni, and Si oxides at the synthesis stage [34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations